A new perspective on the economic valuation of informal care: the well-being approach revisited: SFB 649 Discussion Paper 2013-035 - Kehl, Konstantin; Stahlschmidt, Stephan (SFB 649 discussion paper, 2013)
Informal care has drawn much attention among scholars and policymakers as it concerns an essential but hard to evaluate resource of welfare. Albeit several studies addressed the monetary value of informal care, differences in the relationship between caregivers and recipients have often been ignored. We report on a profound and formerly unobserved distinction between care in the household and non-household care for a family member or in a voluntary framework. According to our results caregivers within the household perceive care as a burden and a positive shadow price arises. By contrast in the family but non-household context - and especially in the voluntary case - care is (at least partly) understood as an enriching experience which extends well-being and leads to negative shadow prices. This distinction calls a marketized view of informal care into question and may contribute to explaining the limitations of monetary incentive policies to encourage informal care.